Causes and relevance of unsatisfactory and satisfactory but limited smears of liquid-based compared with conventional cervical cytology - Siebers,A.G.; Klinkhamer,P.J.J.M.; Vedder,J.E.M.; M. Arbyn; Bulten,J. (Arch.Pathol.Lab Med, 2012)
Context.-Recent randomized controlled trials have shown a significant decrease in unsatisfactory rates for liquid-based cytology (LBC) compared with conventional Papanicolaou test (CP). The underlying causes and relevance of unsatisfactory results for LBC and CP have never been compared within the setting of a randomized controlled trial. Objective.-To examine differences in causes and relevance of unsatisfactory and satisfactory but limited by (SBLB) results for LBC and CP. Design.-Data from the Netherlands ThinPrep Versus Conventional Cytology (NETHCON) trial were used, involving 89 784 women. Causes and relevance of unsatisfactory and SBLB results were analyzed. Results.-The primary cause for unsatisfactory results for CP and LBC was scant cellularity. Other causes for unsatisfactory CPs were virtually eliminated with LBC. The same was true for SBLB subcategories, with the exception of SBLB absence of transformation zone component and SBLB scant cellularity. The SBLB absence of transformation zone component showed a statistically significant 22% and SBLB scant cellularity a 12% nonsignificant increase with LBC. The detection rates of abnormalities found during 18 months of follow-up of unsatisfactory test results did not differ significantly between the 2 study arms, nor did they differ from the initial test positivity rates from the NETHCON trial. Conclusions.-Liquid-based cytology shows an almost complete elimination of most causes for unsatisfactory CP, with scant cellularity remaining as the sole cause for unsatisfactory LBC. On the other hand, with LBC a significant increase of smears without a transformation zone component was noted. Women with an unsatisfactory test result are not at increased risk for cervical abnormalities either with LBC or with CP. Trial Registration.-Nederlands Trial Register, NTR1032, www.trialregister.nl
Keywords: an; AS; at; Belgian Foundation Against Cancer; cervix; cit_Marbyn; conventional; cytology; detection; differences; ECCG; endocervical cells; Follow up; FOLLOW-UP; Hand; Increase; monolayer cytology; Netherlands; ON; PREHDICT; quality of smear; RATES; RCT; Register; result; results; risk; study; Test; The Netherlands; WOMEN